The shedded ectodomain of Lyve-1 expressed on M2-like tumor-associated macrophages inhibits melanoma cell proliferation - Dollt, Claudia; Becker, Kathrin; Michel, Julia; Melchers, Susanne; Weis, Cleo-Aron Thias; Schledzewski, Kai; Krewer, Andreas; Kloss, Loreen; Gebhardt, Christoffer; Utikal, Jochen; Schmieder, Astrid (OncoTarget, 2017)
Targeting immune cells that support tumor growth is an effective therapeutic strategy in tumor entities such as melanoma. M2-like tumor-associated macrophages (TAM) sustain tumor growth by secreting anti-inflammatory cytokines, proteases and growth factors. In this study, we show that a protein derived from M2-like macrophages namely the shedded ectodomain of Lyve-1 (sLyve-1) decreases human HT144 and murine B16F1 melanoma cell proliferation significantly by acting as a decoy receptor for lowmolecular weight hyaluronic acid (LMW-HA) although the LMW-HA/Lyve-1 interaction on lymphatic endothelial cells has been described to induce lymphangiogenesis. This is in line with our finding that the number of LYVE-1+ TAM decreases in higher human melanoma stages and that the early growth of B16 transplant tumors is enhanced in Lyve-1 knockout mice when compared to wild-type mice due to an increased melanoma cell proliferation. LYVE-1 expressing TAM are however true M2 macrophages as they coexpress typical M2-markers such as CD163 and CD206. The results of the present study highlight the necessity to carefully determine the net effect particular TAM subpopulations have on tumors before establishing a treatment to target these immune cells.
Gesehen am 12.07.2018